2022
DOI: 10.1002/jmv.28108
|View full text |Cite
|
Sign up to set email alerts
|

VG161 activates systemic antitumor immunity in pancreatic cancer models as a novel oncolytic herpesvirus expressing multiple immunomodulatory transgenes

Abstract: The VG161 represents the first recombinant oncolytic herpes simplex virus type 1 carrying multiple synergistic antitumor immuno‐modulating factors. Here, we report its antitumor mechanisms and thus provide firm theoretical foundation for the upcoming clinical application in pancreatic cancer. Generally, the VG161‐mediated antitumor outcomes were analyzed by a collaboration of techniques, namely the single‐cell sequencing, airflow‐assisted desorption electrospray ionization‐mass spectrometry imaging (AFADSI‐MSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Oncolytic viruses (OVs) are a powerful tool for fighting cancer. Besides their ability to directly attack and lyse cancer cells, they have also demonstrated an impressive ability to induce a potent and lasting memory immune response against tumors [30][28]. Oncolytic virotherapy relies on tumor cell-specific changes associated with the hallmarks of cancer, including increased receptor expression, impaired antiviral response, and altered metabolism [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oncolytic viruses (OVs) are a powerful tool for fighting cancer. Besides their ability to directly attack and lyse cancer cells, they have also demonstrated an impressive ability to induce a potent and lasting memory immune response against tumors [30][28]. Oncolytic virotherapy relies on tumor cell-specific changes associated with the hallmarks of cancer, including increased receptor expression, impaired antiviral response, and altered metabolism [32].…”
Section: Discussionmentioning
confidence: 99%
“…Viral infection in the tumor microenvironment may also provide a danger signal that partially counteracts the immunosuppressive tumor microenvironment. On the other hand, the BiTE will take advantage of the increased infiltration of T cells into the tumor induced by the OV treatment, which we have demonstrated in previous work [28], [29], promoting T-cell activation and tumor-cell killing in the presence of cells displaying a selected TAA on the cell surface.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our previous results demonstrated that VG161, together with anti-PD-1 monoclonal antibody (mAb), provided better therapeutic performance in PDAC humanized mouse model, and that a significant growth of CD8 + T cells and NK cells were observed in the combination group. 270 A combination of CF-33 and anti-PD-L1 therapy showed durable antigenspecific antitumor immunity and long-term survival against colon cancer in a syngeneic mouse model. 271 Interestingly, Nguyen et al addressed the significance of the timing of anti-PD-1 mAb to be administered in the combination treatment with OV.…”
Section: Combined With Icismentioning
confidence: 98%
“…For example, arginine glycine peptide-human serum albumin-mediated drug nanoparticles show tumor-targeting effects and increase the cytotoxicity of gemcitabine and curcumin[ 160 ]. Administration of VG161, the first recombinant oncolytic herpes simplex virus type 1 that delivers multiple synergistic antitumor immunomodulatory factors, can systematically activate both innate and adaptive immunity and improve the anti-tumor function of the tumor immune microenvironment[ 161 ]. Another study showed that using gold nanoparticles could enhance the intracellular delivery of oncolytic adenoviruses into PC cell lines[ 162 ].…”
Section: Future Perspectivesmentioning
confidence: 99%